9. ASSESSMENT OF THE TREATMENT RESULTS OF NASAL BONE FRACTURES AT 103 MILITARY HOSPITAL (Vietnam Journal of Community Medicine, 2023)
Objectives: Assessment of the results of reduction for patients with nasal bone fractures. Subjects and methods: A prospective and case-by-case descriptive study with clinical intervention was undertaken. The study includes 51 patients with nasal bone fractures undergoing surgery at 103 Military Hospital from March 2022 to September 2023.Results: Male patients account for a higher proportion of 66.7% while female patients account for that of 33.3%, and most are at the age of 16–30 (at 54.9%). Traffic accidents are the major causes with 58.8%. Concerning clinical symptoms: 100% of patients with pain, bruising, and swelling in the nose area; 78.4% of patients with post-traumatic epistaxis; 88.2% of patients with nose deformity; 78.4% of patients with a sharp pain nose fracture score and signs of bone crunching in the nasal bone; 52.9% of patients with combined other injuries, in which type II nasal bone fractures accounting for the highest proportion at 54.9%. Results after treatment: the qualified proportion after 1 month is 88.2%, and after 3 months is 96.1%.Conclusion: Research results show that nasal bone fractures are common in males, mainly caused by traffic accidents. Common clinical symptoms are pain, epistaxis, and nasal pyramid deformity. Reduction of nasal bone fractures is a treatment method that allows the restoration of both aesthetic and physiological functions of the nose.
Keywords: Nasal bone fractures, nasal trauma, nasal surgery.